2004
DOI: 10.1097/01.qai.0000136091.72955.4b
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Study of a Candidate Vaccine Designed Against the B and E Subtypes of HIV-1

Abstract: A phase I/II trial of a candidate vaccine to prevent HIV infection was carried out in Bangkok, Thailand, testing AIDSVAX B/E (VaxGen, Inc., Brisbane, CA), a bivalent subunit vaccine prepared by combining recombinant gp120 from a subtype B virus (HIV-1MN) with gp120 from a subtype E virus (HIV-1A244) in alum adjuvant. The studies provide human data on the immunogenicity of various dose combination of non-subtype B vaccine antigens. The results suggest that AIDSVAX B/E is safe and immunogenic in humans. The opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 19 publications
2
50
0
Order By: Relevance
“…A number of significant conclusions can be drawn from these studies. First, we found that gp120 from the A244 strain of HIV-1, included in the AIDSVAX B/E vaccine, and used in the RV144 trial (42,46,81), could be modified to bind multiple PG9-like antibodies with high affinity provided that the proper carbohydrate (mannose-5) was incorporated. Second, we found that fragments of A244 gp120 (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A number of significant conclusions can be drawn from these studies. First, we found that gp120 from the A244 strain of HIV-1, included in the AIDSVAX B/E vaccine, and used in the RV144 trial (42,46,81), could be modified to bind multiple PG9-like antibodies with high affinity provided that the proper carbohydrate (mannose-5) was incorporated. Second, we found that fragments of A244 gp120 (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These assays were performed at the Thailand Ministry of Public Health (MOPH)-CDC Collaboration laboratory with EDTA-anticoagulated blood. At the VaxGen laboratory, 5 assays were used to measure rgp120 antibody responses: an ELISA for antibody that blocks the binding of A244 to the CD4 coreceptor; an ELISA for anti-A244 V2; an ELISA for anti-A244 V3; an ELISA for anti-gp120 MN/ A244 (mixed) binding antibodies; and an ELISA for MN neutralization [21,22]. Specimens collected at the last immunization visit before the first seropositive sample and 2 weeks after the last immunization visit were assayed for this purpose.…”
Section: Vaccine Administration and Outcome Measurementsmentioning
confidence: 99%
“…The mechanisms responsible for the failure of this vaccine strategy include the high degree of envelope glycosylation which renders much of the surface of monomeric gp120 not accessible to antibodies [5,6 ], the CD4-and CCR5-binding sites being either poorly accessible (CD4) or absent in the absence of CD4 binding (CCR5) [5,6 ] and the high rate of HIV mutation associated with the generation of immune-escape virus mutants [7 ]. Monomeric gp120 has been extensively investigated in the clinical setting [8][9][10] and the protective effect of this vaccine strategy has been evaluated in two phase III efficacy trials in Thailand and the USA. Not surprisingly, these clinical trials have shown no protection against HIV infection [11,12].…”
Section: Hiv Vaccines In Clinical Trialsmentioning
confidence: 99%